2016
DOI: 10.7567/jjap.55.07ke10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonotrode material on grain refining of Mg–3Al and Mg–9Al alloys by ultrasonic melt treatment

Abstract: The new process, nucleation enhanced ultrasonic melt treatment (NEUMT), was proposed to increase the refining efficiency through heterogeneous nucleation by using the sonotrode which has been only concerned with the medium to transfer the ultrasonic energy. In the processing, the metal atoms and/or clusters eroded from the sonotrode were supplied and were simultaneously mixed uniformly into the melt by the ultrasound. These particles act as potential nuclei and refine the structure. The process was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…When Ti-alloy sonotrodes are exposed to molten metals under cavitation, they erode and introduce Ti into the melts, and it has been reported that grains are able to be refined without a separate process for refiner feeding by making good use of this undesirable phenomenon. 6,17,18) However, data on the performance of Ti-alloy sonotrodes in terms of grain refinement by ultrasonicating under fully liquid conditions are still lacking in the literature, and views on the grain refining mechanism are debatable. In Mg(3 9) mass%Al alloys, Youn et al observed that the grain was effectively refined by simply applying ultrasound in a complete melt state using Ti sonotrodes without inoculating the grain refiners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Ti-alloy sonotrodes are exposed to molten metals under cavitation, they erode and introduce Ti into the melts, and it has been reported that grains are able to be refined without a separate process for refiner feeding by making good use of this undesirable phenomenon. 6,17,18) However, data on the performance of Ti-alloy sonotrodes in terms of grain refinement by ultrasonicating under fully liquid conditions are still lacking in the literature, and views on the grain refining mechanism are debatable. In Mg(3 9) mass%Al alloys, Youn et al observed that the grain was effectively refined by simply applying ultrasound in a complete melt state using Ti sonotrodes without inoculating the grain refiners.…”
Section: Introductionmentioning
confidence: 99%
“…It was explained that the atoms and/or clusters parted from the sonotrode by the cavitation erosion react with the melt to form proper intermetallic compounds such as Al 3 Ti that can act as heterogeneous nucleation sites. 18) In Al alloys, Puga et al, 19) Mills et al, 20) and Zou et al 21) reported that grain refinement was achieved by applying ultrasound using Ti-alloy sonotrodes above the liquidus temperatures in AlSi, AlMg, and AlZnMg alloys, respectively. However, despite attempts to explain the experimental results with a cavitation-enhanced nucleation mechanism, little attention has been paid to the effect of Ti as a sonotrode material.…”
Section: Introductionmentioning
confidence: 99%
“…13) Ultrasonic melt treatments have been developed since the 1950s; it has been shown that the application of ultrasound to liquid aluminum (Al) can significantly affect the heat and mass transfer in the liquid metal and solidification process. 14,15) Ultrasonic injection imposed upon the liquid and solidifying Al result in the following phenomena: (i) degassing leading to reduced hydrogen; 6,16) (ii) refinement of primary phase particles and grains. 6,17) In a previous study, the mechanism of grain refinement of ultrasonic melt treatment has been proposed with cavitation-enhanced heterogeneous nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Mg-3Al alloy was chosen to be the base alloy, as it is the major composition with high ductility (Youn et al, 2016). Mg-3Al alloy also equips with enhanced compressive yield strength compared to other Mg alloys (Kumar et al, 2017).…”
Section: Design Proceduresmentioning
confidence: 99%